Genetic Analysis of a Pedigree With Antithrombin and Prothrombin Compound Mutations and Antithrombin Heterozygotes - Zhang, Haiyue; Hu, Yiling; Pan, Dongli; Xv, Yuehua; Shen, Weifeng (Frontiers in Genetics, 2022)
Background and Aims: Antithrombin (AT) is the most important physiological inhibitor in vivo, and coagulation factor II (FII) or prothrombin is a coagulation factor vital to life. The purpose of our research was to illustrate the connection between gene mutations and the corresponding deficiencies of AT and FII. Methods: Functional and molecular analyses were performed. The possible impact of the mutation was analyzed by online bioinformatics software. ClustalX-2.1-win and PyMol/Swiss-Pdb Viewer software were used for conservative analyses and to generate molecular graphic images, respectively. Results: The proband showed a lower limb venous thrombosis and acute pulmonary embolism infarction with reduced AT activity (50%). His mother, with subcutaneous ecchymosis, had reduced activities of AT and FII, of 44 and 5%, respectively. Molecular analysis showed that both the proband and his mother carried c.964A > T (p.Lys322stop) heterozygotes in SERPINC1. The difference was that his mother carried homozygous c.494C > T (p.Thr165Met) in F2, while the proband was wild type. Bioinformatics and model analysis indicated that mutations may destroy the function and structure of AT and FII protein. Conclusion: This study identified a novel mutation of SERPINC1 and a missense mutation of F2, which may be the molecular mechanism leading to AT and FII deficiency in this family. It will help genetic diagnosis and counseling for thrombotic families.